Association Between Outpatient Antibiotic Prescribing Practices and Community-Associated Clostridium difficile Infection. (11th August 2015) - Dantes, Raymund; Mu, Yi; Hicks, Lauri A.; Cohen, Jessica; Bamberg, Wendy; Beldavs, Zintars G.; Dumyati, Ghinwa; Farley, Monica M.; Holzbauer, Stacy; Meek, James; Phipps, Erin; Wilson, Lucy; et al.
Abstract : A modest, 10% reduction in outpatient antibiotic prescribing among U.S. adults could result in a substantial 17% reduction in Clostridium difficile infections that originate in the community. Abstract: Background.  Antibiotic use predisposes patients to Clostridium difficile infections (CDI), and approximately 32% of these infections are community-associated (CA) CDI. The population-level impact of antibiotic use on adult CA-CDI rates is not well described. Methods.  We used 2011 active population- and laboratory-based surveillance data from 9 US geographic locations to identify adult CA-CDI cases, defined as C difficile -positive stool specimens (by toxin or molecular assay) collected from outpatients or from patients ≤3 days after hospital admission. All patients were surveillance area residents and aged ≥20 years with no positive test ≤8 weeks prior and no overnight stay in a healthcare facility ≤12 weeks prior. Outpatient oral antibiotic prescriptions dispensed in 2010 were obtained from the IMS Health Xponent database. Regression models examined the association between outpatient antibiotic prescribing and adult CA-CDI rates. Methods.  Healthcare providers prescribed 5.2 million courses of antibiotics among adults in the surveillance population in 2010, for an average of 0.73 per person. Across surveillance sites, antibiotic prescription rates (0.50–0.88 prescriptions per capita) and unadjusted CA-CDI rates (40.7–139.3 cases per 100 000 persons) varied. In regression modeling, reducing antibiotic prescribing rates by 10% among persons ≥20 years old was associated with a 17% (95% confidence interval, 6.0%–26.3%; P = .032) decrease in CA-CDI rates after adjusting for age, gender, race, and type of diagnostic assay. Reductions in prescribing penicillins and amoxicillin/clavulanic acid were associated with the greatest decreases in CA-CDI rates. Conclusions and Relevance.  Community-associated CDI prevention should include reducing unnecessary outpatient antibiotic use. A modest reduction of 10% in outpatient antibiotic prescribing can have a disproportionate impact on reducing CA-CDI rates.